1993
DOI: 10.1007/bf00168782
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent contractions to NG-nitro-L-arginine methyl ester in the porcine isolated splenic artery are sensitive to cyclooxygenase and lipoxygenase inhibitors

Abstract: The nitric oxide synthase inhibitor, NG-nitro-L-arginine methyl ester (L-NAME), produced large endothelium-dependent contractions in isolated segments of the porcine splenic artery, equivalent to approximately 30% of the maximum responses to 5-hydroxytryptamine (5-HT). These responses were inhibited by 1mM L-arginine, but not by either 1mM D-arginine or the superoxide anion scavenger, superoxide dismutase. However, L-NAME-induced contractions were markedly inhibited by the cyclooxygenase inhibitor, flurbiprofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In the porcine pulmonary artery,¯urbiprofen inhibited both U46619-and L-NAMEinduced contractions. The latter observation is similar to those reported in both the splenic (Lot et al, 1993) and coronary (Nakaike et al, 1995) arteries of the pig, and indicates the involvement of a vasoconstrictor prostanoid. In the human pulmonary artery, however,¯urbiprofen increased U46619induced tone and produced a contraction in the presence of L-NAME (data not shown).…”
Section: The Role Of Nitric Oxide and Prostanoids At Restsupporting
confidence: 89%
See 1 more Smart Citation
“…In the porcine pulmonary artery,¯urbiprofen inhibited both U46619-and L-NAMEinduced contractions. The latter observation is similar to those reported in both the splenic (Lot et al, 1993) and coronary (Nakaike et al, 1995) arteries of the pig, and indicates the involvement of a vasoconstrictor prostanoid. In the human pulmonary artery, however,¯urbiprofen increased U46619induced tone and produced a contraction in the presence of L-NAME (data not shown).…”
Section: The Role Of Nitric Oxide and Prostanoids At Restsupporting
confidence: 89%
“…Pulmonary arteries were located running next to bronchial airways, and carefully followed, cutting away any branches. The arteries were placed in 20 ml of K‐H Solution containing 2% ficoll, which had previously been gassed for 5–10 min with 95% O 2 :5% CO 2 , and stored overnight at 4°C; ficoll was used to prevent osmotic swelling of the cells (Lot et al , 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Such contractile activity is known to occur also in precontracted endotheliumcontaining rings of rat aorta exposed to DCLHb, but to be negligible or absent in such tissues when the basal tone is not first increased by a vasoconstrictor (Muldoon et al 1996). Other evidence suggests that endothelium-derived vasoconstrictor metabolites of arachidonic acid may also participate in the vasoconstrictor effect of Hb (Lot and Wilson 1993). Additional mechanisms through which DCLHb may, at least theoretically, cause a vasoconstrictor effect in isolated blood vessels include the generation of reactive oxygen species secondary to the autooxidation or chemically induced oxidation of DCLHb (Bunn and Forget 1986), the release of endothelin from endothelial cells (Schultz et al 1993;Gulati et al 1995), or direct interaction with drug receptors commonly found in vascular smooth muscle (e.g., α-adrenoceptors, angiotensin receptors, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Receptormediated release of endothelium-derived relaxing factor and PGI 2 are coupled in bovine aortic endothelial cells (BAEC), and several agonists produce vasodilatation through the simultaneous release of NO and PGI 2 (6,14). Radicicol has been shown to inhibit COX-2 expression in smooth muscle cells (5).…”
Section: Role Of the Cox Pathway And Superoxide On The Inhibition Of mentioning
confidence: 99%